Artificial Intelligence Legal Subjects? A Critical Analysis of the Limitations of Modern Legal Personification - Judijanto, Loso; Muptiah, Ojang Oo; Kadir, Taqyuddin (Ipso Jure, 2026)
The development of increasingly autonomous artificial intelligence has challenged the conceptual foundations of modern law, particularly related to the concept of legal subjects and legal accountability mechanisms. The Indonesian legal system until now does not have a specific regulation that explicitly regulates the legal status of artificial intelligence, so the regulation still depends on Law Number 1 of 2024 concerning Electronic Information and Transactions which places artificial intelligence as part of the electronic system. This approach departs from the assumption of human control that is increasingly difficult to maintain as adaptive capabilities and independent decision-making by technology increases. This condition creates a legal vacuum that has an impact on the uncertainty of responsibility attribution when artificial intelligence causes legal consequences. This study aims to critically analyze the position of artificial intelligence in the Indonesian legal system, relevant legal accountability models, and the limitations of modern legal personification. The research method used is normative juridical with a legislative, conceptual, and analytical-critical approach. The results of the study show that granting the status of legal subjects to artificial intelligence has the potential to cause normative distortions and weaken the principle of human accountability. Therefore, legal reform should be directed at strengthening risk-based regulations by affirming human responsibility as the main normative actor, in order to maintain legal certainty and substantive justice.